ANALISIS TINGKAT KESEJAHTERAAN BURUH PERKEBUNAN KELAPA SAWIT DI PT. JALIN VANEO KABUPATEN KAYONG UTARA - Evi Wahyuni; Husni Syahrudin; Bambang Genjik S (Universitas Tanjungpura, 2020)
Abstract This study aimed to, know the income of palm oil plantation company workers in Batu Barat village, Kayong Utara Regency, expenditures level of palm oil plantation campany workers, residence condition of palm oil plantation company workers, know wha health insurance the palm oil plantation company workers family got, ability to send children to school. The author used qualitative reseach which result in written or oral and explain the data through logical reasoning to write logical conclusion about the analysed data also describe the situation sistematically in accordance with the researched phenomenon. Observation, interview, documentation and triangulation techniques was used in data colecting. The result showed that, the workers has low incomes, expenditure level of oil the workers was still insufficient, the workers lived in decent residences, health insurance for workers family members had been guaranteed from the company where they work, the workers ere inable to send their children to school.Keywords: income and expenditure, prosperous, palm oil plantation workers.